PRODUKSI BIOKOMPOSIT DARI RUMPUT GAJAH (PENNISETUM PURPUREUM) HASIL FITOREMEDIASI LIMBAH DENGAN KANDUNGAN KROMIUM MELALUI FERMENTASI FASE PADAT OLEH JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) - Komang Devi Amrita Wirawan, Ni
Environmental damage by chromium metal waste due to the leather tanning process is one of the water pollution in Indonesia. One of the solutions to overcome this environmental pollution is by using a phytoremediation process. Phytoremediation by napier grass is one of the promising alternatives because this plant has a high tolerance for heavy metals and the residues of biomass from phytoremediation can be reused as bioproducts. This study aims to develop the ability of napier grass to remediate chromium weight and utilize its biomass for biocomposite production. Napier grass has been proven to be used as a hyperaccumulator to absorb heavy metal Cr(VI) with an optimal concentration at 20 ppm as indicated by the parameters pH, Total Dissolved Solids (TDS), Relative Growth (RG), plant dry weight, percentage removal, Bioconcentration Factor (BCF), Translocation Factor (TF), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). The TDS value of the medium in this study experienced a decreasing value which indicated that the phytoremediation process could reduce dissolved solids in the medium. Under conditions of 20 ppm Cr(VI) concentration, the highest RG value of stems was 2.71 gram/gram, the highest stem dry weight was 16.47 grams, and the percentage removal for total Cr and Cr(VI) was 99.95%. The value of the BOD/COD ratio in the treatment showed a decrease value from day 0 to day 31 which indicated an increase in media quality after the phytoremediation process lasted for 31 days. The phytoremediation by napier grass plant which was used as a substrate for the growth of the fungus Pleurotus ostreatus in solid-state fermentation for biocomposite production showed a significant fungal mycelium growth. In all treatment of chromium concentration and percentage of inoculum, P. ostreatus showed significant growth which was indicated by an increase in mycelium length and the degree of colonization from day to day, as well as a decrease in the pH value of the substrate which indicated the presence of fermentation activity. The length of the mycelium obtained was in the range of 6.75 – 35.50 mm, the degree of colonization obtained was in the range of 1 – 4, and the final pH value varied in the range of 5.38 – 6.12. The resulting biocomposite has characteristics that are in accordance with several previous studies and specified standards. The value of the water content of the final fermentation substrate, the density of the biocomposite, the water content of the biocomposite, and the water absorption of the biocomposite after soaking for 24 hours were 66.70 – 80.61%; 0.194 – 0.248 g/cm3; 0.52 – 1.58%; and 71.73 – 127.50% respectively. The resulting biocomposite product has the potential to be used as an absorber material in agriculture, especially in facilitate the seed germination process. The heavy metal contained in the biocomposite has been reduced in toxicity through the extracellular mechanism of the fungus P. ostreatus in handling heavy metals and the low concentration of chromium metal did not affect the seed germination process.